Incidence of Pancreatitis Among Dogs in Hyderabad - Sandepogu, Ranjith Kumar; Gadige, Ambica; Kosapati, Lakshmi; Banothu, Anil Kumar (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted from September, 2020 to January, 2021 to study the incidence of canine pancreatitis. The present investigation was undertaken with the primary objective of assessing the occurrence of pancreatitis in dogs and evaluating the comparative effectiveness of two therapeutic regimens in affected animals. A total of 36 dogs showing clinical signs suggestive of pancreatitis were initially screened using the SNAP cPL test kit, which is considered a reliable diagnostic tool for detecting pancreatic lipase levels. Dogs that tested positive were subsequently subjected to detailed diagnostic workups, including complete hematological examination, serum biochemical profiling, and abdominal ultrasonography. In cases where surgical intervention was performed, histopathological evaluation of the pancreas was also carried out to establish a confirmatory diagnosis. Out of the 36 suspected cases, 12 were confirmed to be suffering from pancreatitis, yielding an overall incidence rate of 33.33% in the study population. The distribution of incidence across age groups revealed that older dogs, particularly those above seven years of age, were most frequently affected, accounting for 58.34% of cases. This was followed by dogs in the age range of 2–7 years (33.33%), while younger dogs between 1–2 years showed a lower incidence of 8.33%. Interestingly, no cases were recorded in puppies less than one year of age. Breed-wise analysis demonstrated a higher predisposition in German Shepherds (41.67%), while Pomeranians (25.00%), Golden Retrievers (16.67%), Rottweilers (8.33%), and Dobermanns (8.33%) showed comparatively lower incidences. Sex-wise distribution indicated a greater prevalence in male dogs (66.67%) as compared to females (33.33%), suggesting possible sex-related predisposition factors.